Pseudo-time differentiation trajectory analysis of Trem2+Fcrls+ and Spp1+Cav1+ macrophages from MRL and B6. - Jillian L. McCool (13174542) (2025)
(A) Pseudo-time trajectory analysis was conducted to determine potential origin of Trem2+Fcrls+ and Spp1+Cav1+ macrophages from Ly6c2+ monocytes or tissue resident macrophages. The relative position of cells across the pseudo-time differentiation trajectory is depicted in the figure. Each point is a cell and is colored according to its cluster identity. For both MRL and B6, cells along the trajectory were divided into six groupings based on experimental timepoints (D0-4W). An expansion of Ly6c2+ monocytes along the trajectory towards macrophages was observed after injury, primarily at D1 and D3 in both strains (indicated by arrows). B) Superimposition of the expression of monocyte marker Ly6c2 on the pseudo-time trajectory. Each point is a cell and is colored according to its pseudo-time value. Circle size represents the gene expression level. C) Superimposition of the expression of Arg1, a gene specifically enriched in Spp1+Cav1+ macrophages at D1-D3, on the pseudo-time trajectory. Expansion of cell populations expressing high levels of Arg1 in the monocyte to macrophage direction was observed after injury (indicated by arrows).